Each little bird that sings - Wiles, Deborah (Gulliver Books/Harcourt, 2005)
Comfort Snowberger is well acquainted with death since her family runs the funeral parlor in their small southern town, but even so the ten-year-old is unprepared for the series of heart-wrenching events that begins on the first day of Easter vacation with the sudden death of her beloved great-uncle Edisto.